2016
DOI: 10.1016/j.vetimm.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant materials that enhance bovine γδ T cell responses

Abstract: Despite the availability of vaccines and antibiotics, viral, bacterial and parasite-induced intestinal and pulmonary diseases still cause significant losses to the livestock industry. Excepting improvements in calf survival due to predation, there have been only modest improvements in bovine calf survival since 1991. Strikingly, digestive and respiratory diseases still account for almost half of the non-predator deaths in calves. The innate immune system has evolved to rapidly recognize and respond to invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 87 publications
2
5
0
Order By: Relevance
“…When cytokine expression in mesenteric lymph nodes (MLNs) and spleen cells were measured, the feeding of açai polysaccharides induced expression of IL-12 in supernatant fluids from cultured MLN and spleen cells from the treated mice. IL-12 was also detected in the serum of the mice [127]. Expression of IFNγ was also increased in spleen cells from açai polysaccharide-fed mice, similar to the previous finding using nasal administration [125].…”
Section: A Plant Polysaccharides As γδ T Cell-targeted Immunomodulatorsupporting
confidence: 88%
See 2 more Smart Citations
“…When cytokine expression in mesenteric lymph nodes (MLNs) and spleen cells were measured, the feeding of açai polysaccharides induced expression of IL-12 in supernatant fluids from cultured MLN and spleen cells from the treated mice. IL-12 was also detected in the serum of the mice [127]. Expression of IFNγ was also increased in spleen cells from açai polysaccharide-fed mice, similar to the previous finding using nasal administration [125].…”
Section: A Plant Polysaccharides As γδ T Cell-targeted Immunomodulatorsupporting
confidence: 88%
“…The role of the β-glucan receptor dectin-1 was particularly investigated, since IL-12 is produced by immune cells following ingestion of β-glucans [128]. Our result demonstrated that açai polysaccharides contain appropriate linkages for recognition by dectin-1 using an inhibition ELISA against β-glucan [127]. Furthermore, açai polysaccharides specifically block binding of anti-dectin-1 antibodies to immune cells in a flow cytometry based assay.…”
Section: A Plant Polysaccharides As γδ T Cell-targeted Immunomodulatormentioning
confidence: 80%
See 1 more Smart Citation
“…Knowledge about γδ T cell populations in the horse is scarce. Studies in other species have established that γδ T cells are innate immune cells with antigen-presenting and cytolytic functions [92]. A transient increase in the γδ T cell population occurs in calves over the first 2 months, perhaps similar to that suggested by the equine transcriptome dataset presented here; overall γδ T cells comprise approximately 40% of calf PBMCs at birth and then decline to adult cow levels (approximately 15%) by 5 months of age [93].…”
Section: Resultssupporting
confidence: 68%
“…A dose of 1 mg/L AMP-B corresponds to approximately 1.08 µM, which is sufficient to increase the cytotoxicity of NK cells according to our current study. AMP-B is also suggested as an adjuvant molecule for murine and bovine γδ T cell responses [16]. In this report, AMP-B injection into mice increased IFN-γ production, which could be produced by NK cells and T cells.…”
Section: Discussionmentioning
confidence: 64%